Why So Contrived? Fourth Amendment Balancing, Per Se Rules, and DNA Databases After Maryland v. King - Kaye, David H. (2014)
In Maryland v. King, 133 S. Ct. 1958 (2013), the Supreme Court narrowly upheld the constitutionality of routine collection and storage of DNA samples and profiles from arrestees. In doing so, it stepped outside the usual framework that treats warrantless searches as per se unconstitutional unless they fall within specified exceptions to the warrant and probable cause requirements. Instead, the Court balanced various individual and state interests. Yet, as regards the state interests, the Court confined this direct balancing analysis to the perceived value of using DNA to inform certain pretrial decisions. Oddly, it avoided relying directly on DNA’s more obvious value in generating investigative leads in unsolved crimes. This Article suggests that this contrived analysis resulted from the structure of existing Fourth Amendment case law (and perhaps a desire to avoid intimating that a more egalitarian and extensive DNA database system also would be constitutional). It demonstrates that the opinion does not support a “no lines” system of ad hoc judgments about the reasonableness of every search using the totality of the circumstances. Recognizing that the existing framework of categorical exceptions to the warrant requirement diverges from an older “warrant preference” rule that demands a warrant whenever feasible, the Article shows that King leaves the current per se framework largely intact. Nevertheless, this Article questions the resort to direct balancing. It presents a more coherent doctrinal framework for scrutinizing not just DNA profiling, but all forms of biometric data collection and analysis. In this regard, it notes that the dissenting King opinion overstates the differences between fingerprinting and DNA profiling as currently practiced. Finally, it suggests that the cramped reasoning in both opinions limits the implications of the case for more aggressive DNA database laws — ones that cover more crimes, more people, more loci, and more methods for acquiring DNA samples